Peranan Orang Tua Terhadap Kepercayaan Diri Anak dalam Meningkatkan Prestasi - Sukmayanti; Yustin, Jeremy; Ai, Salsa; Rahmadanti, Fira; Gusvina, Felisitas (UNIVERSITAS SERAMBI MEKKAH, 2024)
This writing aims to fulfill the assignment for the Quatitative Research Methods course by investigating the role of parents in children’s self- confidence in increasing achievement. This research emphasizes how parental support, communication, and parenting style can shape children’s self confidences. As primary educators, parents have a great responbility to provide moral, emotional support and opportunities for childres to reach their own potential. Research shows that childres’s sel – confidence increases witf the right parenting approach and good examples from parents. This has a positive impact on the child’s academic performance. Strong self- confidence makes children brayer in facting difficulties and encouranges them to learn.